Use of connected injection device has a positive effect on catch-up growth in patients with growth disorders treated with growth hormone therapy - de Arriba, Antonio; van Dommelen, Paula; Savage, Martin O. (Frontiers in Endocrinology, 2024)
Human growth hormone (hGH) therapy in children can be administered by subcutaneous injection using either a manual non-connected device, which is a portable injection pen loaded with a pre-filled cartridge, or an electronic connected device. The electronic device is connected to a platform where adherence data is recorded and available for health care professionals (HCPs) and patient support programs. Real-world data used in the clinic, includes regular monitoring of adherence data which are shared with families during patients' visits and aim to determine the root causes of poor adherence. This study aimed to identify whether there are differences in growth during the first four years of treatment depending on the device, i.e. non-connected versus connected devices. This retrospective study reports treatment of either GH deficiency or short stature secondary to birth size small for gestational age (SGA) in 174 pediatric patients attending Miguel Servet Hospital, Zaragoza, Spain. hGH treatment was administered with manual non-connected devices in 87 patients and 87 patients used connected devices. Height was followed for 4 years after start of hGH therapy. In total, 57% of subjects had GHD and 43% were SGA. Height standard deviation score (HSDS) at treatment start was higher (p<0.001) in the non-connected device group compared to the connected device group. Change of HSDS in the connected device group was significantly higher in the second (+0.13), third (+0.20) and fourth (+0.23) year of treatment compared to the non-connected group after adjustment for age and HSDS at treatment start, sex, indication, dose and Tanner stages during treatment, and timing of measurements. In conclusion, these results support the use of the connected device for hGH treatment of pediatric growth disorders.